Peran Penerapan Model Problem Based Learning (PBL) terhadap Kemampuan Literasi Matematis dan Kemandirian Belajar - Rahmat Hidayat; Yenita Roza; Atma Murni (JURING (Journal for Research in Mathematics Learning), 2018)
This article is based on the low ability of mathematical literacy and learning independence of learners. This article aims to describe the role of the PBL model of mathematical literacy and learning independence. The type of research used in this article is quantitative descriptive research conducted on students of class VIII MTs Darul Wasi'ah Simalinyang through interviews with learners and teachers, observation, and literature review analyzed descriptively.